The morality of treason - Fabre, C (Springer, 2020)
Treason is one of the most serious legal offences that there are, in most if not all jurisdictions. Laws against treason are rooted in deep-seated moral revulsion about acts which, in the political realm, are paradigmatic examples of breaches of loyalty. Yet, it is not altogether clear what treason consists in: someone’s traitor is often another’s loyalist. In this paper, my aim is twofold: to offer a plausible conceptual account of treason, and to partly rehabilitate traitors. I focus on informational treason, as the act of passing secret intelligence to foreign actors without authorization. I argue that informational treason is sometimes justified, indeed morally mandatory; even when it is morally wrong, its beneficiaries are sometimes justified, indeed obliged, to make use of the intelligence thereby provided.